Microneedle radiofrequency for skin rejuvenation: bridging image-derived metrics and photographic assessment - Malarz, Dajana; Czyżewski, Łukasz; Olczak-Kowalczyk, Dorota (Frontiers in Medicine, 2025)
PurposeTo analyze the condition of the skin before and after microneedle radiofrequency (RF) treatment and to identify a series of cascade changes occurring within its structure. Additionally, to test whether regular home care modifies treatment effects and to corroborate objective changes with blinded Global Aesthetic Improvement Scale (GAIS) ratings.Materials and methodsA retrospective analysis was conducted using photographs of 38 women taken before and after a single microneedle RF treatment and 15 untreated controls. The images were captured using the Observ 520× device at baseline and 30 days post-procedure. Quantitative assessment of changes was performed with ImageJ software. The GAIS was used to evaluate visible changes in the photographs under blinding to group and time. The primary endpoint was the change score (Δ = post−pre) for pigmentation, vascular parameters, and hydration across forehead/right/left cheek. Primary analysis used ANCOVA with robust (HC3) errors, adjusting for age and baseline, including home care (regular vs. sporadic/none), a group ×home-care interaction, and false discovery rate (FDR) control.ResultsAmong the participants, at least 84.2% showed improvement in skin tone, reduction of pathological erythema, and increased skin hydration. GAIS distributions were bimodal (improvement 1–3 only in RF; no change/worsening 4–5 only in controls; χ2p < 0.001). Unadjusted between-group contrasts favored RF across 9/9 outcomes with large effects. In adjusted models, RF showed an independent benefit for forehead vascular parameters; critically, a significant group × home-care interaction (p = 0.003) indicated greater pigmentary gains with regular daily skincare, with hydration showing a similar borderline trend. No serious adverse events were recorded.ConclusionMicroneedle RF is an effective method for reducing wrinkles and improving image-derived pigmentation, vascular, and hydration metrics at 30 days, with a low complication rate. Regular home care functions as a clinically meaningful response amplifier, particularly for pigmentation- supporting protocolized post-procedure skincare to maximize outcomes. Findings are associative (non-randomized design); replication in randomized, adherence-controlled studies is warranted. Generalizability is limited (women aged 35–50, single center, predominantly Fitzpatrick I–III); extrapolation to men and darker phototypes (IV–VI) is not warranted.